In vitro effect of apelin on contractions and endothelial-independent relaxation in the human internal mammary artery - Kacar, E.; Burma, O.; Ulker, N.; Yardimci, A.; Uysal, A.; Elestimur, H. K. (Wiley-Blackwell, 2014)
[Abstract Not Available]